An Optimum Strategy for Producing Precise GPS Satellite Orbits using Double-Differenced Observations (Journal of Engineering, 2018)
Both the double-differenced and zero-differenced GNSS positioning strategies have been widely used by the geodesists for different geodetic applications which are demanded for reliable and precise positions. A closer inspection of the requirements of these two GNSS positioning techniques, the zero-differenced positioning, which is known as Precise Point Positioning (PPP), has gained a special importance due to three main reasons. Firstly, the effective applications of PPP for geodetic purposes and precise applications depend entirely on the availability of the precise satellite products which consist of precise satellite orbital elements, precise satellite clock corrections, and Earth orientation parameters. Secondly, the PPP processing strategy has been employed by the International GNSS Service (IGS) and IGS analysis centers to evaluate their products in terms of homogeneity and precision over a long period of time. Thirdly, the precise positions, which are determined using PPP technique, and are referenced directly to the geodetic reference frame of the satellite orbital parameters. Thus, the definition of the geodetic datum of the site coordinates using different strategies plays an enormous role in the process of generation satellite orbital parameters which have to be compatible with the corresponding satellite clock corrections and the Earth orientation parameters. This study focuses on producing uninterrupted series of satellite orbit and clock products using different criteria and assesses these products using PPP. The double-difference processing technique was used to achieve the goal of this study by Bernese GPS software version 5.0. Twenty-two globally distributed IGS stations were selected to run PPP based on the generated products and then compare the results with corresponding PPP results which were created based on the IGS rapid products. The comparison pointed to a significant improvement in the generated precise products which have considerably increased the precision of positions. What is more, this study stated that there is an observable agreement between the horizontal positions accuracies which are generated using different techniques for modeling the reference frame.